(untitled) - National Research Council; Institute of Laboratory Animal Resources.,Subcommittee on Dog and Cat Standards (Washington, 1973)
This book provides many of the general points are applicable to dogs in any environment and in this respect it provides a comprehensive survey of acquisition, facilities and management of the dog
Keywords: Dogs as laboratory animals